Wink Poppy Midnight - Tucholke, April Genevieve (Speak, 2017)
Every story needs a hero. Every story needs a villain. Every story needs a secret. Wink is the odd, mysterious neighbor girl, wild red hair and freckles. Poppy is the blond bully and the beautiful, manipulative high school queen bee. Midnight is the sweet, uncertain boy caught between them. Wink. Poppy. Midnight. Two girls. One boy. What really happened? Someone knows. Someone is lying.